A Dog Model of Pancreaticojejunostomy Without Duct-to-Mucosa Anastomosis - Choi, Sung Hoon; Choi, Jun Jeong; Kang, Chang Moo; Hwang, Ho Kyoung; Lee, Woo Jung (JOP. Journal of the Pancreas, 2012)
<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: Batang; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">Context<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: Batang; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US"> Various anastomosis techniques have been introduced for the safe pancreaticoenterostomy. Objective In the present study, we developed an experimental animal model for simple pancreaticojejunostomy and evaluated the feasibility, safety, and efficacy of this technique. Animals Ten dogs were studied. Intervention The dogs underwent the simple approximation (“docking”) method for pancreaticojejunostomy and were re-explored on the 30th post-operative day. Main outcome measure After excision of the remnant pancreas with the jejunal segment of the pancreaticojejunostomy, the degrees of fibrosis in the remnant pancreas were analyzed according to the patency of the pancreaticojejunostomy. Results There were no mortalities and clinically significant complications. The patency of pancreaticojejunostomy remained in six cases and was obliterated in four cases. It was noted that obliterated pancreaticojejunostomy accompanied cases with more dilated pancreatic ducts (3.1±0.4 mm vs. 5.5±0.6 mm, P=0.008). The grade of pancreatic fibrosis was significantly correlated with the obliterated pancreaticojejunostomy (P=0.038) and the size change of the remnant pancreatic duct (P=0.040). Conclusions The suggested simple pancreaticojejunostomy method is easy and shows no evidence of significant pancreatic fistula. However, the potential risk of dysfunction in the remnant pancreas limits its possible clinical applications. The meticulous duct-to-mucosa pancreaticojejunostomy is highly preferred to manage the remnant pancreas following pancreaticoduodenectomy.